Interaction between butterflies (Lepidoptera: Nymphalidae) and longhorn beetle (Coleoptera: Cerambycidae), with comments on the use of exudate as a food resource - Dantas, Caique; Ferreira, Gabriel S.; Zacca, Thamara (Entomological Communications, 2023)
The interaction between the butterfly Fountainea glycerium cratais (Hewitson, 1874) and the longhorn beetle Retrachydes thoracicus thoracicus (Olivier, 1790), simultaneously feeding on the exudate of the Schinus tree (Anacardiaceae), is herein reported. We also revised the literature on this topic and compile data of other species of butterflies and beetles performing the similar type of ecological interaction in Neotropical region. Although this type of interaction has been documented as commensalism in some literature, the paucity of observations limits this affirmation and the development of standardized studies considering the frequency of occurrences and the behavior of the species involved are on demand.